Distribution and Abundance of Eel Larvae (Anguilla spp.) in the Coastal Waters of Malunda, West Sulawesi - Tenriware; Nur, Muhammad; Jabbar, Firmansyah Bin Abd; Husniah; Jufri, Ady (Indonesian Journal of Ecology and Conservation, 2024)
This study aimed to identify the abundance of eel larvae in the coastal waters of Malunda, West Sulawesi Province. Sampling of eel larvae was conducted in the coastal waters of Malunda, West Sulawesi. A hand scoop net (seser) with a mesh size of 1 mm was used as the sampling gear. Sampling activities were carried out once a month at night during the new moon phase. The captured samples were placed in buckets containing river water equipped with an aerator and then transported alive to the Integrated Laboratory of Universitas Sulawesi Barat for identification and measurement of body length and weight. Water quality parameters, including salinity, pH, temperature, and total dissolved solids (TDS), were measured during each sampling event. Species identification was conducted using the Anal–Dorsal Vertebrae (ADV) key character method by counting the number of anodorsal vertebrae and measuring the anodorsal length. The results showed that the eel larvae found in the coastal waters of Malunda consisted of a single species, Anguilla marmorata. The specimens obtained had an anodorsal vertebrae count ranging from 14 to 18. The highest abundance of eel larvae was recorded in August. The environmental conditions of the Malunda coastal waters are still considered suitable for the survival and optimal growth of eel populations